2022
DOI: 10.1002/1878-0261.13268
|View full text |Cite
|
Sign up to set email alerts
|

Cellular senescence and the tumour microenvironment

Abstract: The senescence‐associated secretory phenotype (SASP), where senescent cells produce a variety of secreted proteins including inflammatory cytokines, chemokines, matrix remodelling factors, growth factors and so on, plays pivotal but varying roles in the tumour microenvironment. The effects of SASP on the surrounding microenvironment depend on the cell type and process of cellular senescence induction, which is often associated with innate immunity. Via SASP‐mediated paracrine effects, senescent cells can remod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 214 publications
0
28
0
Order By: Relevance
“…The risk score characterized by distinct mutation profiles. cells (24). Therefore, CS-related genes may affect the TME.…”
Section: Discussionmentioning
confidence: 99%
“…The risk score characterized by distinct mutation profiles. cells (24). Therefore, CS-related genes may affect the TME.…”
Section: Discussionmentioning
confidence: 99%
“…Telomere attrition to a critical threshold length that is no longer able to sustain telomere integrity is one of several known inducers of cellular senescence [50]. This type of senescence, termed telomere-induced or replicative senescence, can be triggered by the well-known tumour suppressor p53 and its downstream effector p21, a cyclin-dependent kinase inhibitor that represses the cell cycle (as discussed in an accompanying article in this special series [51,52]). Mathematical models and studies of budding yeast have suggested that the shortest telomeres are responsible for senescence induction [53,54].…”
Section: Telomere Erosion: a Harbinger Of Senescencementioning
confidence: 99%
“…Senescent cells secret specific small molecules or exosomes (EV) that interact with and influence the nearby environment. This phenomenon is known more generally as the Senescence-Associated Secretory Phenotype (SASP) and is a phenotype common to many senescent states, including that induced by eroded telomeres (please see accompanying review) [51,52,62,65,66] (Fig. 2).…”
Section: Telomere Erosion: a Harbinger Of Senescencementioning
confidence: 99%
“…Senescence-associated proliferation arrest and SASP cooperate in tumor suppression, by arresting proliferation of damaged pre-malignant cells and promoting immune clearance. Although senescence is acutely tumor suppressive, over the longer term, as a source of chronic inflammation, SASP also promotes tissue aging and disease, as reviewed by Rugang Zhang and colleagues [52] and Naoko Ohtani and colleagues [53].…”
Section: Other Potential Causes Of Age-associated Cancermentioning
confidence: 99%